PENERAPAN METODE PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE,REVIEW) DALAM MENINGKATKATKAN KETERAMPILAN MEMBACA PESERTA DIDIK KELAS XI BAHASA SMA NEGERI 1 DRIYOREJO GRESIK - Kalawen, Merlin; Wahyuningsih, Fahmi (LATERNE, 2022)
Reading is a skill that must be mastered by foreign language learners such as German. Reading is an easy thing to do. However, reading comprehension in German is quite difficult for students of class XI Language at SMAN 1 Driyorejo. Students have difficulty reading because of lack of vocabulary mastery/Wortschatz, not accustomed to reading German texts, low interest in reading German, boring and inappropriate learning methods. This is known when the author observed directly during the Introduction to the School Field (PLP) conducted a survey by giving reading texts to students to test their reading skills. Therefore, educators need to apply various learning methods that can improve students' reading skills. One method that can be used in learning reading skills is the PQ4R method. The formulation of the problem in this study is, How is the process of applying the PQ4R method in reading comprehension of descriptive text in German class XI at SMA Negeri 1 Driyorejo? The purpose of this study was to describe the prose of the application of the PQ4R method of reading comprehension skills in German class XI students of SMA Negeri 1 Driyorejo. This research use desciptive qualitative approach. The main data of this study were taken from the results of observations and questionnaires as supporting data. Sources of data in this study were students of class XI Language SMAN 1 Driyorejo. Good observations, then from the results of student questionnaires which said that by using this method students can better understand reading and are also more active in learning. From these results, it can be concluded that the PQ4R method can be applied to the reading comprehension skills of class XI students of SMAN 1 Driyorejo.